EHD2 Overexpression Suppresses the Proliferation, Migration, and Invasion in Human Colon Cancer. (21st April 2021) - Guan, Chengqi; Lu, Cuihua; Xiao, Mingbing; Chen, Weichang
Abstract: Background: To investigate how EHD2 influences the development of colon cancer. Methods: Immunohistochemistry of 90 colon cancer tissue specimens were determined the expression of EHD2. The lentivirus-EHD2-transfected colon cancer cells were conducted to evaluate the biological behaviors. Results: EHD2 was closely associated with clinic pathological parameters ( p  < 0.001). EHD2 upregulation was relative with a longer overall survival. The results of the univariate and multivariate analyses indicated that EHD2 could be an independent prognosis marker. EHD2 overexpression suppressed cell invasion and proliferation, but enhanced cell apoptosis and cell cycle arrest. Conclusions: EHD2 might represent a therapeutic target of colon cancer. IMPACT STATEMENT: What is already known on this subject? Membrane trafficking is crucial for cell proliferation, differentiation and apoptosis, especially tumorigenesis and development. EHD2 proteins play an important role in the regulation of membrane trafficking in endocytosis. EHD2 has been suggested to participate in the occurrence of some malignancies. What are the new findings? EHD2 could be an independent prognosis marker in colon cancer. EHD2 overexpression suppressed cell invasion and proliferation, but enhanced cell apoptosis and cell cycle arrest in vitro . EHD2 overexpression markedly increased the expression of EMT marker E-cadherin in colon cancer. How might it impact on clinical practice in the foreseeable future? EHD2 overexpression may inhibit tumorigenesis in colon cancer through the modulation of E-cadherin, the critical marker of EMT which is closely related to invasion and distant metastasis of tumor cells.